Child Maltreatment Protection : A Comparative Analysis with the United Kingdom and United States in Addressing OCSEA - Sasono, Satryo; Septiano, Fatih Afrisal Bagus; Putri, Delasari Krisda (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The development of digital technology, particularly social media, has had a significant impact on children's lives. The digital world has become a new platform for crime, particularly online sexual exploitation and abuse of children (OCSEA). This study focuses on identifying the role of families and regulations in supporting children's digital world, as well as evaluating regulations as a preventive measure to prevent behavioral deviations and violence. A multidisciplinary approach between psychology and law, using qualitative research methods through legal analysis and literature review. The study findings indicate that active users of digital media among children and adolescents experience psychological changes when spending their daily time online to access information, entertainment, communication, and even pornographic content using Virtual Private Networks (VPNs). Legal violations such as sextortion, cyberbullying, misuse of personal data, grooming, and child trafficking through digital platforms are on the rise, making the protection of children from exploitation in the digital world a critical issue. International regulations include the UNCRC, ICCPR, and Indonesia through Law Number. 35 of 2014 on Child Protection; (2) Law Number. 19 of 2016 on Electronic Information and Transactions are not yet effective enough to address the social phenomena of gender inequality and violence when compared to child protection efforts in countries such as the United States, the European Union, and the United Kingdom, which have more inclusive regulations.